PENGARUH KEPUASAN PEGAWAI DAN TINGKAT KEDISIPLINAN TERHADAP PRESTASI KERJA PEGAWAI KECAMATAN BENOWO KOTA SURABAYA - Rohmah Kurniawati (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
This research's objective was finding out how employee satisfaction and workplace discipline levels impacted productivity in the Benowo District of Surabaya. Descriptive quantitative research methodology was applied in this study. there were 34 people chosen randomly as the population in this study, which is 65% total population used as a sample. In this study, questionnaire were used in collecting the data. This study applied the multiple linear regression analysis technique to process the data. Computer and SPSS 23 program were used in processing the data. The findings of this research indicate that the t test for job satisfaction variable (X1) obtained t arithmetic > from t table is 6.504> 1.697, while the variable level of discipline (X2) obtained t arithmetic > from t table that is 2.913> 1.697. Additionally, the results of the F test were 84.301> 3.32 and a significance of 0.000, which is derived from the F table using F arithmetic. Thus, the variable work performance (Y) in Benowo District, Surabaya, was positively impacted by the variables job satisfaction (X1) and level of discipline (X2), partially and concurrently